2015
DOI: 10.5603/cj.a2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Renal function impairment predicts mortality in patients with chronic heart failure treated with resynchronization therapy

Abstract: Background: The use of cardiac resynchronization therapy (CRT) and implantable cardioverter-defibrillator (ICD) for advanced heart failure (HF) is increasing. Renal dysfunction is a common condition in (Cardiol J 2015; 22, 4: 459-466)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A number of studies have shown that chronic kidney disease (CKD) is associated with high cardiovascular mortality as a result of accelerated atherosclerosis. An increased predisposition to atherosclerosis is largely driven by chronic inflammation, oxidative stress, and dyslipidaemia, which are usually associated with CKD [1,2,3]. The dyslipidemia of CKD patients is classically characterized by hypertriglyceridemia and a low concentration of high-density lipoprotein cholesterol (HDL-C) associated with normal or slightly reduced low-density lipoprotein cholesterol (LDL-C) levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that chronic kidney disease (CKD) is associated with high cardiovascular mortality as a result of accelerated atherosclerosis. An increased predisposition to atherosclerosis is largely driven by chronic inflammation, oxidative stress, and dyslipidaemia, which are usually associated with CKD [1,2,3]. The dyslipidemia of CKD patients is classically characterized by hypertriglyceridemia and a low concentration of high-density lipoprotein cholesterol (HDL-C) associated with normal or slightly reduced low-density lipoprotein cholesterol (LDL-C) levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Acute decompensated HF often causes acute pre-renal kidney failure due to decreased blood flow through the kidneys. Chronic HF also often co-exists with chronic kidney failure, which is associated with increased activity of the renin-angiotensin-aldosterone system, oxidative stress, inflammation, and increased activity of the sympathetic nervous system [15]. These are the cornerstones of cardiorenal syndrome patho- Table 2.…”
Section: Our Analysis Of 638 Decompensated Hf Patients Demonstratesmentioning
confidence: 99%
“…There are very few studies investigating the role of CRT in the improvement of renal function in patients with HF and chronic renal dysfunction [14,36]. An observational study revealed that patients with baseline CKD showed an improvement in eGFR (mean change: 4.24±14.2 mL/min/1.73 m 2 ), and patients without baseline CKD showed a decrease in GFR (mean change eGFR: 3.01±20.9 mL/min/1.73 m 2 ) [14]. Recently, a study including 260 patients demonstrated that the severity of baseline CKD was significantly associated with an increased risk of death, transplantation, or left ventricular assist device [37].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 178 studies were excluded at the title/abstract level, and 31 studies were excluded at the full text level, according to the criteria mentioned above. As a result, 16 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] satisfied our inclusion criteria and were included in our analysis.…”
Section: Studies and Patientsmentioning
confidence: 99%